1987
DOI: 10.1073/pnas.84.22.7856
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of beta-hydroxylated asparagine residues in non-vitamin K-dependent proteins containing epidermal growth factor-like domains.

Abstract: Vitamin K-dependent bovine protein S has been shown to contain a posttranslationally hydroxylated asparagine within a conserved sequence in three of its epidermal growth factor (EGF)-like domains. In a review of amino acid sequences deduced from cDNA data, we have observed that a conserved sequence containing a potential asparagine hydroxylation site exists within EGF-like domains of a variety of functionally diverse proteins. We have studied a number of these and report the presence of erythro-j8-hydroxyaspar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(46 citation statements)
references
References 36 publications
5
41
0
Order By: Relevance
“…1). Plasma factor IX and each recombinant protein had similar Gla content (10.7-11.4 residues) as measured by the technique of Przysiecki et al (43). The amino-terminal sequence of each mutant protein was also 5 One unit/ml of factor VIII after IIa activation contains ϳ0.7 nM factor IXa binding sites (see "Results and Discussion").…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Plasma factor IX and each recombinant protein had similar Gla content (10.7-11.4 residues) as measured by the technique of Przysiecki et al (43). The amino-terminal sequence of each mutant protein was also 5 One unit/ml of factor VIII after IIa activation contains ϳ0.7 nM factor IXa binding sites (see "Results and Discussion").…”
Section: Resultsmentioning
confidence: 99%
“…Circulating factor IX consists of an amino-terminal ␥-carboxyglutamic acid (Gla) 1 domain (residues 1-40), a short hydrophobic segment (residues [41][42][43][44][45][46], two epidermal growth factor (EGF)-like domains (EGF1 residues 47-84 and EGF2 residues 85-127), an activation peptide region (residues 146 -180), and the carboxyl-terminal serine protease domain (residues 181-415). Based upon the crystal structure of the Gla domain of factor VIIa (8), the Ca 2ϩ binding properties of factor X, 2 and the NMR structure of the Gla domain of factor IX (10), it would appear that this domain in factor IX possesses several low to intermediate affinity Ca 2ϩ binding sites.…”
mentioning
confidence: 99%
“…We predict that these type C sequences are hydroxylated on the appropriate aspartate or asparagine residue (see Figure 3) and bind Ca2>. Recently amino acid analysis has shown that uromodulin, thrombospondin and thrombomodulin (Przysiecki et al, 1987) contain detectable levels of (-hydroxyasparagine, although the exact location remains to be determined.…”
Section: Equivalent Sites In Other Proteinsmentioning
confidence: 99%
“…Immunoblotting was performed using a chemiluminescence detection system employing a peroxidase-conjugated polyclonal F.IX antibody. Gla analysis was performed according to the modified alkaline hydrolysis method of Price (16). Amino-terminal protein sequence analysis was performed by automated Edman degradation to confirm the mutation at position 12.…”
Section: Analysis Of Proteinmentioning
confidence: 99%